Gas-filled capillary-discharge stabilization for plasma-based accelerators by means of a laser pulse. (8th October 2021) - Biagioni, A; Anania, M P; Arjmand, S; Behar, E; Costa, G; Del Dotto, A; Ferrario, M; Galletti, M; Lollo, V; Pellegrini, D; Di Pirro, G; Pompili, R; et al.
Abstract: The development of compact accelerator machines is leading towards the use of plasma-based devices that are able to sustain large acceleration gradients up to several tens of GV m −1 . The main issue, in this regard, is due to the necessity to produce the plasma shot-by-shot starting from neutral gases, since its lifetime is limited to a few tens of microseconds. This puts severe limitations on its resulting uniformity, stability and reproducibility, which in turn strongly affects the quality of accelerated beams by plasmas. In this work, we describe a gas-filled discharge-capillary where the plasma generation, achieved by ionizing Hydrogen gas with a high-voltage electrical discharge, is stabilized by triggering its ignition with an external laser pulse. Results show a noticeable stabilization of the resulting plasma density along the capillary and the discharge pulse. This enables the development of very long capillaries and in turn, acceleration lengths as required, for instance, by next-generation plasma-based facilities delivering beams in the GeV-scale.